Shaping the Future of Dentistry: How Digital VR-Haptic Thinkers Are Revolutionizing Education by Thinking Big for Better Future in Oral Care - Chau, Reinhard Chun Wang; Neshka, Manchorova; Pantea, Mihaela; Rampf, Sarah; Liukkonen, Mikko; Rice, David R.; Morton, David; Bandiaky, Octave Nadile; Nagasawa, Masako; Bágyi, Kinga; Quinn, Barry F.; Carramolino-Cuéllar, Esther; Galán-Gil, Sónnica; Flacco, Nicla; Pasqualini, Damiano; Shazib, Muhammad A.; Schick, Simona-Georgiana; Yarmukhamedov, Bekhzod; Ackerman, Kristin; Arias-Herrera, Santiago; Palotie, Ulla-E; Kada, Ahmed Adam; Bouyahyaoui, Nawal; Quenta-Silva, Edgar; Rederiene, Gitana; Arrouf, Nisrine El; Rodríguez-Hopp, María P.; Suominen, Anna L.; Edgar, Hannelie; Shanks, Nicola; Jackson, Amanda; Hendron, Brid; Usta, Sila Nur; Lingström, Peter; Örtengren, Ulf; Maggio, Margrit; Sondagar, Niku; Abuzaid, Maxstein M.; Ponto-Wolska, Małgorzata; Lam, Walter Yu Hang; Regulski, Piotr A.; Huhtela, Outi; Zadrożny, Łukasz; Pang, Mengwei; Bergman, Suzie; Felszeghy, Szabolcs; Bencharit, Sompop; Sittoni-Pino, Maria F. (European Journal of Dentistry, 2025)
Integrating digital, virtual reality (VR), and haptic technologies into dental education transforms training by fostering immersive, student-centered environments. These tools bridge theoretical knowledge and clinical practice, enhancing psychomotor skills, reducing anxiety, and enabling standardized assessments in risk-free settings. The Digital, VR, and Haptic Thinkers Network drives global collaboration and innovation. Drawing on insights from a 2025 conference at Queen Mary University of London, this commentary explores advancements, challenges, and future directions for VR-haptic integration in dental curricula. Results from global implementations, including improved manual dexterity and procedural precision, as well as enhanced pulpotomy performance, demonstrate a significant educational benefit. In clinical dentistry, VR-haptic simulators enhance patient outcomes by facilitating precise skill development for procedures in restorative dentistry and endodontics, thereby reducing errors in real-world practice. Combining these technologies with traditional methods is proposed to prepare competent, confident dental professionals while addressing educational disparities. Rigorous validation, strategic curriculum integration, and interdisciplinary collaboration are recommended to maximize impact.
Keywords: dental education; virtual reality; haptic technologies; digital; artificial intelligence; psychomotor skills; curriculum integration